Speaking up for democracy: Experiences with dialogue formats in public spaces (Pedagogical Horizons, 2025)
Liberal democracies are on the brink. Some voters support the transformation of democracy into autocracy, other citizens are worried about it. This article discusses democracy talks – streetworking for democracy – as a low-threshold approach of civic education in public spaces. Based on a specific grassroot-initiative, it describes and analyzes the conditions, possibilities, and practices for strengthening democratic attitudes and political forces using the dialogue method. The result: the concept of democracy cannot remain abstractly institutional and procedural in discussion formats, but must be approached from a daily life perspective. Streetworking for democracy is more than just listening; statements that reject democracy and are hostile to social groups must be contradicted. This requires time, passion, and further training.
Keywords: dialogue formats; resilient democracy; low-threshold democracy education; street work for democracy; civil society